Towards an integrative approach for ecodesign principles and sustainable material selection: A systematic literature review to explore scholarly contributions at the intersection of materials, sustainable design and household appliances - Ferraresi, Stefano; Del Curto, Barbara (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Through a systematic literature review the scholarly contributions at the intersection of ecodesign, sustainable material selection, and the household appliance sector are explored. A comprehensive search was conducted on the Scopus database, yielding 181 initial results, which were narrowed down to 52 relevant documents for in-depth analysis. Notably, the review revealed a growing research interest in these areas, particularly since 2015, reflecting broader industry trends towards circular and sustainable production models. Key findings include the identification of eco-innovation drivers, approaches for sustainable product design and assessment, and the importance of validating research outcomes through real-world case studies. The analysis also pointed out an evolution in sustainable design strategies and material selection focus, shifting from sole materials recycling towards durability, repair and life-extension. Some overarching themes emerged across the reviewed documents, including the application of Life-Cycle-Thinking approaches together with LCA-based methods and a general push to foster the implementation of ecodesign strategies in early design phases to maximize their effectiveness. The review also allowed to identify and visualize a network of scholars focused on appliance-related research works. A significant finding is the relative scarcity of research that effectively aim at integrating ecodesign and material selection specifically for the appliance industry.